Assessing xeriscaping as a sustainable heat island mitigation approach for a desert city - CHOW, Winston T. L. (Institutional Knowledge at Singapore Management University, 2012)
Metropolitan Phoenix has been amongst the most rapidly urbanizing cities in the USA, and is also subject to an urban heat island (UHI) of significant intensity and extent. There is a need to mitigate its detrimental effects through sustainable methods, such as through the application of low-water demand, xerophytic trees with broad canopies within residential yards (i.e. xeriscaping). Urban xeriscaping has the potential to reduce urban water use, urban temperatures and outdoor thermal discomfort, but evaluating its effectiveness has not been widely researched. In this study, we used a micro-scale urban climate model (ENVI-met) to generate xeriscaping scenarios in two residential areas with different existing surface vegetation cover (mesic vs. xeric). We subsequently examined the resulting impacts of xeriscaping on near-surface temperatures and outdoor thermal comfort over different spatial scales and temporal periods. Compared to existing conditions, xerophytic shade trees have strong UHI mitigation potential in existing xeric residential areas in Phoenix, with greater cooling occurring at (i.) microscales (∼2.5 °C) vs. local-scales (∼1.1 °C), and during (ii.) nocturnal (0500 h) vs. daytime periods (1700 h) under high xeriscaping scenarios. Conversely, increased xeriscaping resulted in net warming and increased thermal discomfort over mesic residential neighborhoods over all spatial scales and temporal periods. These varying results over different residential land cover in Phoenix therefore must be considered by stakeholders when considering xeriscaping as a UHI mitigation method.